Dynamics of Female Teacher Mover in the Learning Community - Ervina Halit; Sarmini Sarmini; M. Jacky; Sugeng Harianto; Agus Suprijono (CV. Syntax Corporation Indonesia, 2024)
The role of women in education is increasingly important, especially in the context of career development and leadership. This study aims to look at the dynamics of women in the Teacher Mover program in learning communities, including the challenges faced, the seniority dilemma, and their role in curriculum implementation. The research approach used is qualitative with a phenomenological design. The research subjects consisted of female teachers who have graduated and have a Teacher Mover certificate. Data collection techniques were conducted through interviews and documentation, followed by data analysis through data reduction, presentation, and verification. The results show that (1) women's struggles in the Teacher Mover program include a rigorous selection process and six months of training; (2) the dilemma faced relates to the perception of seniority in the school that often doubts their abilities; and (3) the presence of women as Teacher Mover proves significant in leading learning and contributing to seminars related to the independent curriculum. This research highlights the importance of environmental support for women's career development in education, as well as the need for policies that strengthen women's position in learning communities. The findings are expected to provide insights for the development of more inclusive education policies.